Effect of solvent types on phenolics content and antioxidant activities of Acacia polyacantha gum - MohammedElnour, A. A. Hassan; Mirghani, Mohamed Elwathig Saeed; Kabbashi, Nassereldeen Ahmed; Alam, Md Zahangir; Musa, Khalid Hamid; Abdullah, Aminah (Faculty of Food Science & Technology, Universiti Putra Malaysia (UPM), 2017)
Acacia polyacantha gum (APG) is a dried exudate which obtained from the stems and branches of Acacia polyacantha trees. APG is rich in soluble dietary fibers as well as organic compounds. In this study quantitation of the levels of total phenolics content (TPC) and antioxidant activities were conducted using ABTS and CUPRAC assays for APG extraction using pure solvents (methanol, ethanol, acetone) and their aqueous mixtures at 50% and 100%. The antioxidant levels were evaluated by 2,2’-azino-bis-(3-mthylbenzothiazoline-6-sulfonic acid) (ABTS+) radical cation deculturization and cupric iron reducing capacity in the presence of neocuproine (CUPRAC) for the evaluation of reducing power, and (TPC) was evaluated by the Folin-Ciocalteu method. The solvent Methanol (50%) gave the best extraction ratio for APG presented by highest (TPC 60.78 mg GAE/100g of DW, CUPRAC 34.65 mg TE/100g DW, and, ABTS about 37.65 mg TE/100g DW respectively), followed by ethanol 50% extract. On the other hand, pure methanol showed the lowest TPC 5.33 mg GAE/100g of DW, ABTS 10.9 mg TE/100g DW, and CUPRAC 7.80 mg TE/100g DW, values respectively. Therefore, the variation in the antioxidant capacity of extracts was possibly due to the difference of polarity, immiscibility and the nature of the APG compounds extracted using various solvents. The higher content of antioxidant activity in APG shall be useful to human health if it is properly utilized.